The Effectiveness of Visual-Based Learning Strategies in Improving Clinical Reasoning of Medical Professional Students: Literature Review - Risa Hude Umar; Shulhana Mokhtar; Silva Sari Indah Catur (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2026)
Background: Medical education aims to produce physicians with strong clinical competencies, including clinical reasoning skills. Visual-based learning strategies, such as images, videos, virtual simulations, and virtual patients, are considered effective in enhancing these skills through more concrete, contextual, and interactive learning experiences. However, the effectiveness of different visual learning methods in improving clinical reasoning abilities among medical students remains an area that requires further investigation. Methods: This study employed a literature review design using a systematic search approach based on the PICOS framework. Relevant articles were identified through Google Scholar, PubMed, Garuda, and ScienceDirect databases using keywords related to visual learning, clinical reasoning, and medical students. The review included studies published between 2021 and 2025 that examined the effectiveness of visual-based learning strategies among medical profession students. Data were analyzed using descriptive and narrative synthesis methods. Results: The findings indicate that visual-based learning strategies are generally effective in enhancing clinical reasoning skills among medical students. Interactive approaches, particularly virtual simulations and virtual patient-based learning, demonstrate greater effectiveness compared to passive visual methods such as educational videos. In addition to improving clinical reasoning, visual-based learning strategies also contribute to the development of clinical observation skills, critical thinking, communication abilities, and empathy toward patients. Conclusion: Visual-based learning strategies are effective in improving clinical reasoning skills among medical profession students, especially when integrated with active and interactive learning approaches. The effectiveness of these strategies is influenced by the type of visual media used and the instructional design implemented. Therefore, the integration of interactive visual learning methods is recommended to support the development of clinical competencies in medical education.